2020
DOI: 10.1016/j.avsg.2020.06.046
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Covid-19 Patient with Acute Limb Ischemia and Heparin Resistance

Abstract: Heparin resistance is an uncommon phenomenon defined as the need for high-dose unfractionated heparin (UFH) of more than 35,000 IU/day to achieve the target activated partialthromboplastin time ratio or the failure to achieve the desired activated clotting time after a full UFH dose. This rare phenomenon is being more commonly observed in Covid-19 patients in a hypercoagulable state. We describe a Covid-19 patient confirmed by reversetranscriptase polymerase chain reaction assay, with acute limb ischemia, who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 12 publications
2
28
3
Order By: Relevance
“…However, his condition was resistant to treatment, and tended to recur. This finding is in correlation with reports by others [ 2 , [6] , [7] , [8] ]. Bellosta and colleagues [ 6 ] described 20 patients (18 men) with COVID-19-associated ALI over a period of 3 months.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, his condition was resistant to treatment, and tended to recur. This finding is in correlation with reports by others [ 2 , [6] , [7] , [8] ]. Bellosta and colleagues [ 6 ] described 20 patients (18 men) with COVID-19-associated ALI over a period of 3 months.…”
Section: Discussionsupporting
confidence: 94%
“…The other patient, a man aged 37 years with upper extremity thrombosis was successfully managed with UFH administration [ 7 ]. Baccellieri and colleagues [ 8 ] reported a patient who developed COVID-19-associated ALI while under prophylactic LMWH. The 67-year-old man with no relevant medical history was successfully treated with surgical intervention for simultaneous lower and upper limb ischemia [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…7,31 Distributed between short and isolated records, more frequent arterial involvement was shown in the lower limbs, predominantly the popliteal, anterior and posterior tibial, superficial femoral, iliac, and distal aorta. 7,12,23,24,26,28,[32][33][34] This distribution coincides with our findings where these arteries were mainly counting about 50% of the total of vessels involved.…”
Section: Discussionsupporting
confidence: 92%
“…18,21,22 ALI in COVID-19 can occur in two situations. During the in-hospital evolution of severe COVID-19 infection 6,[23][24][25][26] , Zhan et al has reported a median of 19 (11-23 days) from the appearance of symptoms of the infection to the installation of ischemia 27 or they can be admitted to the emergency room for this vascular condition with mild or no respiratory symptoms. [28][29][30] We report an ischemic time of 39 hours, defined from the apparent onset of symptoms to surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation